1992
DOI: 10.1002/yea.320080103
|View full text |Cite
|
Sign up to set email alerts
|

Yeast flocculation: Reconciliation of physiological and genetic viewpoints

Abstract: Yeast flocculation results from surface expression of specific proteins (lectins). Two flocculation phenotypes were suggested by physiological and biochemical tests, whereas genetic data suggested a larger number of mechanisms of flocculation. After reviewing the biochemistry, physiology and genetics of flocculation, a new hypothesis combining the data available from these different sources, is proposed. Flocculation results when lectins present on flocculent cell walls bind to sugar residues of neighbouring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1
6

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 93 publications
2
41
1
6
Order By: Relevance
“…The sensitivity of flocculation to mannose and/or glucose is explained by the lectin theory, which states that lectin-like protein on one cell binds in a Ca-dependent way to sugar receptors on a neighbouring cell. The MS group corresponds to the Flo1 phenotype, while the GMS group corresponds to the NewFlo phenotype (reviewed by Stratford, 1992). The FLO1 gene is one constituent of the Flo1 phenotype (Teunissen et al, 1993;Watari et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of flocculation to mannose and/or glucose is explained by the lectin theory, which states that lectin-like protein on one cell binds in a Ca-dependent way to sugar receptors on a neighbouring cell. The MS group corresponds to the Flo1 phenotype, while the GMS group corresponds to the NewFlo phenotype (reviewed by Stratford, 1992). The FLO1 gene is one constituent of the Flo1 phenotype (Teunissen et al, 1993;Watari et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Flocculation determined by the FLO5 (Bidard et al, 1994) and FLO8 genes also belong phenotypically to the Flo1/MS group (Masy et al, 1992). No genetic determinants have been described or cloned for the NewFlo group, although it is anticipated that the gene(s) involved should code as well for a lectin-like protein (Stratford, 1992). Little is known about the mechanism of flocculation in MI strains.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to elucidate the FLO2 function. Some controversial data has involved the dominant FLO8 gene [87][88][89][90][91][92][93]. Finally, Kobayashi and collaborators [94] cloned the FLO8 gene and their results suggested that the FLO8 gene mediates flocculation via transcriptional activation of the FLO1 gene.…”
Section: Genetics Of Yeast Flocculationmentioning
confidence: 99%
“…It was reported by Straver et al (1994) that two flocculation phenotypes were distinguished by sugar inhibition, and further, they suggested the existence of at least two distinct lectin-encoding flocculation genes. To date, many genetic studies on flocculation in S. cerevisiae have reported several chromosomal genes affecting flocculation (for reviews, see Stratford, 1992;Watari et al,1994b).FLO1, which is one of the dominant flocculation genes, has been cloned and sequenced by three groups (Bidard et al, 1995;Teunissen et al, 1993;Watari et al, 1994b). Recently it was shown that FLO1 should be a structural gene coding for a cell surface protein, which has a key role in the mechanism of yeast flocculation, because of the localization of its product (Bidard et al, 1995), the similarity of the N-terminal sequence between the putative FLO1 product and a protein that was purified from flocculent yeast cell surface, and the stimulative effect on the flocculation ability of the yeast cells (Straver, 1994 Bunkyo-ku, Tokyo 113-8657, Japan (Received July 17, 1998; Accepted October 8, 1998) A nonflocculent industrial polyploid yeast strain, Saccharomyces cerevisiae 396-9-6V, was converted to a flocculent one by introducing a functional FLO1 gene at the URA3 locus.…”
mentioning
confidence: 99%
“…It was reported by Straver et al (1994) that two flocculation phenotypes were distinguished by sugar inhibition, and further, they suggested the existence of at least two distinct lectin-encoding flocculation genes. To date, many genetic studies on flocculation in S. cerevisiae have reported several chromosomal genes affecting flocculation (for reviews, see Stratford, 1992;Watari et al,1994b).…”
mentioning
confidence: 99%